Interaction of the Sun and the Moon: A New Look - Pavlenko, Anatolii (Advances in Social Sciences Research Journal, 2026)
The adequacy of our understanding of Nature is proportional to our knowledge of the laws operating in it. The article describes the phenomena that cannot be described from the point of view of orthodox physics. It is assumed that the "fundamental" physical theory to be developed should be able to include the intelligent consciousness of elementary particles. This theory will allow us to reach a deeper level of description of physical phenomena. Prominent British physicist, Nobel Prize laureate Roger Penrose points out that this new, as yet absent theory, must be "uncomputable", that is, so that its action cannot be modeled by a Turing machine. The practical results described in the article may advance theoretical ideas for the creation of a new physical "fundamental" theory. Fundamental, applied, and technological research in the field of torsion (taxion, etc.) fields is only at the beginning of its journey. Like any new direction in science and technology, it is vulnerable to criticism, since the number of emerging questions greatly exceeds the number of available answers. This line of inquiry may allow us to reach a deeper level of description of physical phenomena. The focus on torsion (taxion) fields as a nascent area of research highlights both the challenges and the potential for groundbreaking discoveries in physics.